2022
DOI: 10.3389/fbioe.2021.814246
|View full text |Cite
|
Sign up to set email alerts
|

Improved Release of Monosaccharides and Ferulic Acid Using Enzyme Blends From Aspergillus Niger and Eupenicillium Parvum

Abstract: Supplementing commercial xylanase and cellulase with selected debranching enzymes only resulted in slight enhancement of the enzymatic hydrolysis of wheat bran autohydrolysis residues (WBAR) which was obtained at 160°C over a 30-min period of autohdyrolysis, while a blend of enzymes from Aspergillus niger and Eupenicillium parvum achieved synergistic efficacy in this context. Using an equal mixture blend of these enzymes at a 0.5% (w/w) enzyme loading dosage with the addition of ferulic acid esterase (1 U/g su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The CMCase activity, xylanase activity, and FAE activity of FA12 were measured on the third day of five consecutive passages. The kinds of phenolic acids released by the microbial consortium and the amount of FA release were studied by LC–MS qualitative and quantitative analysis . At the same time, the weight loss rate and changes of four components (cellulose, hemicellulose, acid-insoluble lignin, and acid-soluble lignin) during the microbial treatment were determined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CMCase activity, xylanase activity, and FAE activity of FA12 were measured on the third day of five consecutive passages. The kinds of phenolic acids released by the microbial consortium and the amount of FA release were studied by LC–MS qualitative and quantitative analysis . At the same time, the weight loss rate and changes of four components (cellulose, hemicellulose, acid-insoluble lignin, and acid-soluble lignin) during the microbial treatment were determined.…”
Section: Methodsmentioning
confidence: 99%
“…The kinds of phenolic acids released by the microbial consortium and the amount of FA release were studied by LC−MS qualitative and quantitative analysis. 22 At the same time, the weight loss rate and changes of four components (cellulose, hemicellulose, acid-insoluble lignin, and acidsoluble lignin) during the microbial treatment were determined. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) were used to study the change in the structure characteristics of the distiller's grains before and after microbial treatment.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This compound combination of specific depolymerizing carbohydrases, also called zymogram, synergistically acts on AX, aiding in the release of monosaccharides and the improvement of the degradation rate [ 9 , 10 ]. Therefore, EA removes the arabinose residues in order to expose more cleavage sites and enhance EX accessibility [ 11 , 12 ], while EF cleaves ferulic acid ester bonds cross-linked to arabinose residues in order to liberate ferulic acid [ 13 , 14 ]. Accordingly, our previous work systematically demonstrated that water-extractable AX and water-unextractable AX were hydrolyzed more effectively in vitro by the special xylanase collaborations with EA and EF [ 10 ].…”
Section: Introductionmentioning
confidence: 99%